A STUDY ON THE EMERGING TRENDS OF DATA JOURNALISM AND ENVIRONMENT IN INDIA - Sharma, Siddharth; Mishra, Pranav; Dubey, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There is a belief that Data journalism is relatively a new term for environmental practices, but in fact, the relation of environment and data goes way long back than one can think. Now more advanced and visual methods have replaced the older one and due to which the relation between the two variables is more visible. Environment and data were always related. But with the advances in computer-based reporting, the use of data in environmental reporting has excelled. With the increasing population and human penetration in nature, has resulted in many issues that for which mankind can be blamed. Now whenever any environment is affected the numbers of casualties are huge. Not only casualties but everything it touches is huge, be the damage, the geography it covered, anything. It becomes a huge task for the journalist to compile that whole data and show it in understandable manner. Because, until and unless the proper message is conveyed, people won’t be able to understand the gravity of the disaster. And to combat this problem of dealing huge chunk of data is data journalism. In this chapter we will see how data journalism was used to show the environmental issues.